The role of black locust (Robinia pseudoacacia L.) in establishment of short-rotation energy plantations in Hungary - Rédei, K.; Veperdi, I. (International Journal of Horticultural Science, 2009)
Establishment of short-rotation energy plantations for fuel production has been of international interest for many years. Energy plantation experiments in Hungary have been conducted for a longer time. In the country black locust ( Robinia ps eudoacacia L.) is one of the most important stand-forming tree species, covering approximately 23% of the forested land (410 000 ha) and providing about 19% of the annual timber output of the country. This fast growing species seems to be suitable for energy plantations as well. So, in Helvecia (Central Hungary, sand-soil region) two energy plantation s were established u sing common black locust and its cultivars improved in Hungary. The spacing variations of the common black locust were: l.5x0.3 m, I .5x0.5 m and l.5x 1.0 m. At the age of 5 the closest spacing ( 1.5x0.3m) produced the greatest annual increment in oven-dry weight (6.5 t ha·1 yr- 1). In the trial with black locust cultivars planted in spacing of 1.5xl.0m, at the age of 7 the highest annual increment in oven-dry mass was produced by the cultivar ’ Ulloi’ (9.7 t ha-1 yr- 1) followed by the common black locust (8.4 t ha-1 yr- 1) and the cultivar ’J tiszkiseri (1.6 t ha·1 yr- 1). The trials have verified that in temperate climate the increment in oven dry dendromass of black locust energy plantation s has ranged from 6 to 12 t ha·1 yr·1. On the basis of the trials’ evaluation the quantity of dendromass mostly depends on site quality, species and cultivars, as well as on the initial spacing (plants per hectare).